Investigation of the Content and Dynamics of Nutrients In The Surface Water of Lake Mulehe In Kisoro District, South-Western Uganda. - Saturday, Alex (Kabale University, 2023)
Water pollution with nutrient-based contaminants is a major concern as it may lead to the eutrophication of freshwater bodies. The purpose of this study was to investigate the content and dynamics of nutrients in the shallow (max. 6 m) Lake Mulehe. We collected 54 water samples from nine sampling stations between the wet season March–May 2020 and the dry season (June–August 2020). Nutrients; ammonia–nitrogen (NH4–N), nitrate–nitrogen (NO3–N), nitrite–nitrogen (NO2–N), total nitrogen (TN), total phosphorus (TP) and soluble reactive phosphorus (SRP) were investigated in accordance with APHA 2017 standard procedures. Besides, physical parameters: Temperature, pH, turbidity, electrical conductivity and dissolved oxygen were measured in situ. The water quality index (WQI) was used to determine the water quality of Lake Muhele using drinking water quality standards developed by the Uganda National Bureau of Standards and the World Health Organization. Results indicated that nutrients (TN, NO3–N, TP, NH4-N, NO2–N and SRP) did not differ substantially between study stations (p > 0.05) but did reveal significant differences (p < 0.05) across study months. Besides, nutrient levels differed significantly between seasons (p < 0.05) except for SRP and NH4–N. The WQI values varied from 36.0 to 74.5, with a mean of 58.69. The recorded overall WQI value places Lake Mulehe’s water quality into the ‘poor’ category in terms of worthiness for human consumption. The study, therefore, recommends continuous pollution monitoring and enforcement of local regulations to reduce pollution in the lake as a result of anthropogenic activities.